Sex-Related Differences in Protein Expression in Sarcomere Mutation-Positive Hypertrophic Cardiomyopathy - Schuldt, Maike; Dorsch, Larissa M.; Knol, Jaco C.; Pham, Thang V.; Schelfhorst, Tim; Piersma, Sander R.; dos Remedios, Cris; Michels, Michelle; Jimenez, Connie R.; Kuster, Diederik W. D.; van der Velden, Jolanda (Frontiers in Cardiovascular Medicine, 2021)
Background: Sex-differences in clinical presentation contribute to the phenotypic heterogeneity of hypertrophic cardiomyopathy (HCM) patients. While disease prevalence is higher in men, women present with more severe diastolic dysfunction and worse survival. Until today, little is known about the cellular differences underlying sex-differences in clinical presentation. Methods: To define sex-differences at the protein level, we performed a proteomic analysis in cardiac tissue obtained during myectomy surgery to relieve left ventricular outflow tract obstruction of age-matched female and male HCM patients harboring a sarcomere mutation (n = 13 in both groups). Furthermore, these samples were compared to 8 non-failing controls. Women presented with more severe diastolic dysfunction. Results: Out of 2099 quantified proteins, direct comparison of male, and female HCM samples revealed only 46 significantly differentially expressed proteins. Increased levels of tubulin and heat shock proteins were observed in female compared to male HCM patients. Western blot analyses confirmed higher levels of tubulin in female HCM samples. In addition, proteins involved in carbohydrate metabolism were significantly lower in female compared to male samples. Furthermore, we found lower levels of translational proteins specifically in male HCM samples. The disease-specificity of these changes were confirmed by a second analysis in which we compared female and male samples separately to non-failing control samples. Transcription factor analysis showed that sex hormone-dependent transcription factors may contribute to differential protein expression, but do not explain the majority of protein changes observed between male and female HCM samples. Conclusion: In conclusion, based on our proteomics analyses we propose that increased levels of tubulin partly underlie more severe diastolic dysfunction in women compared to men. Since heat shock proteins have cardioprotective effects, elevated levels of heat shock proteins in females may contribute to later disease onset in woman, while reduced protein turnover in men may lead to the accumulation of damaged proteins which in turn affects proper cellular function.